PENINGKATAN KETERAMPILAN MENULIS TEKS NEGOSIASI DENGAN MEDIA AUDIO-VISUAL PADA SISWA KELAS X TSM I SMK MUHAMMADIYAH 3 YOGYAKARTA TAHUN PELAJARAN 2014/2015 - Amelya Rizcki Agusta; Siti Rochmiyati (CARAKA, 2016)
This study aimed to describe (1) the increase in the activity of the students in writing the negotiating text by audio-visual (2) increase students' skills in writing the negotiating text by audio-visual media in class X Muhammadiyah 3 Yogyakarta. 26 research subjects’ students. The object of research in the form of learning writing skills negotiating text with audio-visual media in the learning process of students of class X SMK Muhammadiyah 3 Yogyakarta in writing independently negotiating text. The results showed that Methods of data collection in this study using observation, interviews, documentation, and testing. This study uses data validity is content validity and reliability rater. (1) an increase in the activity of students on aspects of students' activity learning pre-cycle 53.84%, 84.61% first cycle and second cycle 88.46%. Attention pre-cycle 69.23%, 73.07% first cycle and second cycle 92.30%. Understanding of the material pre-cycle 42.30%, 76.92% first cycle and second cycle 96.15%. The pre-cycle seriousness of 34.61%, 61.53% first cycle, and the cycle II 84.61% and (2) an increase in the activity of students writing students who completed the negotiating text pre-cycle 30.76%, 80.76% first cycle, and second cycle 100%.